Report on practice in industry training in fish processing technology. - De La Llana, Jurelac A. (College of Fisheries, University of the Philippines, 1979)
Smoking is one of the earliest methods of food preservation known to man. Ancient men discovered it accidentally by hanging their food over the fire. They found out that upon doing so, there was an improvement in flavor and that their food lasted longer. Smoking today involves 4 interrelated steps namely salting, precooking, drying and smoking. The process preserves the fish mainly by the first three steps. Smoke has only little preservative effect against spoilage organisms. The purpose of exposure to smoke is to impart a smoky flavor and to give an attractive golden brown color to the fish. Traditionally, 2 basic methods have been used in the smoking process for the preservation of fish. The "cold smoke process" where the fish are smoked at a temperature between 22℃ and 33℃ and the "hot smoked process" where the temperature starts at a temperature of 49℃ and gradually increasing to 80℃ to 90℃ at 10 or 15 minutes intervals. The latter, which is also known as "barbeque smoking" is commonly practiced here in the Philippines. Hot smoked products have a high moisture content ranging from 50 to 70%, hence it is only semi-preserved. They are therefore, more appropriately eaten after processing since they are prone to spoilage or microbial decomposition by bacteria, yeast and molds.